PARAFAC approach to channel estimation in intelligent reflective surface-enhanced mimo systems - Chi, Xinyuan (Nanyang Technological University, 2025)
The integration of Intelligent Reflective Surfaces (IRS) into future wireless communication systems, particularly in instances like Multiple-Input MultipleOutput (MIMO) configurations, promises substantial performance enhancements. However, effective channel estimation remains a critical challenge due to the complex interactions in IRS-assisted systems. This dissertation proposes two robust PARAFAC-based channel estimation methods to address this issue: a closed-form solution using Least Squares Khatri-Rao Factorization (LSKRF) and an iterative solution employing Bilinear Alternating Least Squares (BALS). Both methods exploit the structured nature of the pilot signals and the IRS phase shifts to achieve efficient and accurate channel estimation. The numerical simulations prove that the suggested methods are superior than others in different scenarios, demonstrating significant improvements in estimation accuracy compared to existing techniques.